The importance of travelling wave components in standing surface acoustic wave (SSAW) systems. Issue 19 (8th September 2016) - Devendran, Citsabehsan; Albrecht, Thomas; Brenker, Jason; Alan, Tuncay; Neild, Adrian
Abstract : The dominant forcing mechanism for particle manipulation using SSAW is shown to be spatially dependent when travelling components are considered. Abstract : The use of ultrasonic fields to manipulate particles, cells and droplets has become widespread in lab on a chip (LOC) systems. There are two dominant actuation methods, the use of bulk acoustic waves (BAW) or surface acoustic waves (SAW). The development of BAW actuated systems have been underpinned by a robust understanding of the link between the ultrasonic field and forces which can be generated. In this work, we examine this link for standing surface acoustic waves (SSAW) comparing the relative strengths of streaming induced drag and acoustic radiation forces on suspended particles. To achieve this we have employed boundary conditions which accurately capture the travelling wave components of the pseudo-standing wave field, describe the key features of the acoustic radiation force fields and the acoustic streaming fields which can be generated, and finally we show that the relative importance of these two mechanisms is spatially dependant within a fluid chamber. The boundary condition used models the SSAW as two counter-propagating travelling waves, rather than assuming a standing wave directly. This allows the accurate inclusion of energy decay as the SAW couples into the fluid chamber and the resulting travelling wave component. This study shows that this previously neglected complexity of the SAW field is a critical factor in the nature of the resultant streaming field, as it gives rise to strong streaming rolls at the channel walls, which we validate experimentally. These rolls result in spatial variations of the dominant forces which in turn varies particle migration patterns spatially across the fluid domain.